The relationship between extracurricular sports participation and subjective well-being in junior high school students: a moderated mediation model - Li, Feifei; Li, Liqiang; Du, Xiaomin; Wang, Xiaozan (Frontiers in Public Health, 2024)
Objective To investigate the direct effect of extracurricular sports participation on subjective well-being among junior high school students, and the mediating role of emotion regulation and moderating role of physical education (PE) class participation. Methods Using data from the Program for International Student Assessment (PISA), we analyzed the extracurricular sports participation, emotion regulation, subjective well-being, and PE class participation of 113,203 junior high school students. Results After controlling for country, gender, and health status, extracurricular sports participation significantly predicts subjective well-being. Emotion regulation mediates the relationship between extracurricular sports participation and subjective well-being. Both the direct effect of extracurricular sports participation on subjective well-being and the mediating effect of emotion regulation are moderated by PE class participation. The effect is stronger among students with high PE class participation compared to those with low participation. Conclusion There is a moderated mediation effect between extracurricular sports participation and subjective well-being among junior high school students. Emotion regulation mediates this relationship, while PE class participation enhances the impact of emotion regulation on subjective well-being.